2001
DOI: 10.1034/j.1600-0714.2001.300201.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of premalignant potential in oral lichen planus using interphase cytogenetics

Abstract: This study attempted to evaluate whether oral lichen planus (OLP) has the potential to progress to oral squamous cell carcinoma (OSCC) by comparing the degree of genetic instability between clinically-curable OLP and lesions that progressed to OSCC. Fifteen cases of steroid-responsive OLP and two cases of lichenoid dysplasia (LD) that progressed to OSCC were used for this study. Chromosome in situ hybridization (CISH) was performed for chromosomes 9 and 17. The fraction of polysomic and monosomic cells for chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…To uncover some of the molecular genetic aberrations associated with OLP, investigators have used molecular and genetic methods such as loss of heterozygosity (LOH) (Zhang et al, 2000), chromosome in situ hybridization (Kim et al, 2001), p53 and c-erbB2 expression (Girod et al, 1994(Girod et al, , 1995Kilpi et al, 1996;Ogmundsdottir et al, 2002), and telomerase activity (O'Flatharta et al, 2002). However, none of these methods appears to provide definitive predictive information with regard to the malignant potential of a lesion diagnosed as OLP.…”
Section: Chromosomal Numerical Aberrations In Oral Lichen Planusmentioning
confidence: 97%
See 1 more Smart Citation
“…To uncover some of the molecular genetic aberrations associated with OLP, investigators have used molecular and genetic methods such as loss of heterozygosity (LOH) (Zhang et al, 2000), chromosome in situ hybridization (Kim et al, 2001), p53 and c-erbB2 expression (Girod et al, 1994(Girod et al, , 1995Kilpi et al, 1996;Ogmundsdottir et al, 2002), and telomerase activity (O'Flatharta et al, 2002). However, none of these methods appears to provide definitive predictive information with regard to the malignant potential of a lesion diagnosed as OLP.…”
Section: Chromosomal Numerical Aberrations In Oral Lichen Planusmentioning
confidence: 97%
“…In head and neck cancer, and particularly in OSCC, the incidence of aneuploidy is high (up to 80% of cases) (Stell, 1991;Milroy et al, 1997;Wennerberg et al, 1998;Bockmühl and Petersen, 2002) and has been found to be an early event in humans as well as in animal models (Remmerbach et al, 2001;Maraki et al, 2004;Raimondi et al, 2005;Pektas et al, 2006). Kim et al (2001), using chromosomal in situ hybridization, found a certain extent of genetic instability for chromosome 9 in OLP. Nevertheless, the study used biopsy-based material and is therefore not suitable for clinical follow-up, where a non-invasive approach is required.…”
Section: Chromosomal Numerical Aberrations In Oral Lichen Planusmentioning
confidence: 98%
“…In 1997, ZHANG et al 25 showed that a loss of heterozygosity (LOH) on chromosomes arms 3p, 9p and 17p is found in 6% of OLP patients. In addition, chromosome 9 monosomy was demonstrated to play a critical role in progress to malignancy in two cases of lichenoid dysplasia 14 . More recently, FEMIANO et al 7 found 5% DNA aneuploidy in patients with OLP.…”
mentioning
confidence: 98%
“…Two investigated specific chromosome alterations, and another aimed to detect gross genomic damage 7,14,25 . In 1997, ZHANG et al 25 showed that a loss of heterozygosity (LOH) on chromosomes arms 3p, 9p and 17p is found in 6% of OLP patients.…”
mentioning
confidence: 99%
“…The possibility of malignant transformation is a reflection of many intrinsic molecular alterations within cells, all of which are found in lichenoid dysplasia. 43 Kim et al 44 (2001) assessed the malignant potential of oral lichen planus by comparing the degree of genetic instability in clinically cured cases and in those that had undergone malignant transformation. These authors concluded that lichenoid dysplasia should be seen as a high-risk premalignant lesion, and that chromosome nine monossomia may have an important role in the malignant transformation of this lesion.…”
Section: Malignant Potentialmentioning
confidence: 99%